Jurisdiction in On-line Defamation and Violations of Privacy: In Search of a Right Balance - Kramberger Škerl Jerca (LeXonomica, 2017)
This article will address the rules of EU private international law regarding the international jurisdiction in defamation and the violations of the right to privacy committed via the internet. Being that there is no common conflict of laws rule regarding these issues and a number of different courts hold jurisdiction, great efforts are being taken to prevent the so called ‘forum shopping’, or, as regards to defamation, ‘libel tourism’. It is namely very hard to strike a fair balance between the procedural rights of both parties, since this is strongly connected with striking a balance between the freedom of speech, on one hand, and personality rights, on the other, all of which are fundamental rights. During the internet era, the problems regarding cross-border issues on defamation and privacy cases rose to a whole new dimension. The interpretation of the traditional connecting factor, the place where the harmful event occurred, became very difficult. Over the years, the Court of Justice of the EU has issued several milestone judgments interpreting Article 7(2) of the Brussels I Recast Regulation in such a way that the particularities of violations committed via the internet are taken into account.